IgE/IgG1 antibody responses to ubiquitin are associated with emergency room attendance due to asthma symptoms - Juan Felipe López-Crespo; Dilia Mercado; Velky Ahumada-Contreras; Ronald Regino-López; Josefina Zakzuk-Sierra; Luis Caraballo (Revista Alergia México, 2018)
Background: We had previously identified an IgE-binding low molecular weight component in the house dust mite Blomia tropicalis, identified by Edman degradation as ubiquitin. After cloning its sequence from a cDNA library, we found the protein as 100 % identical to the human orthologous.